Consideraciones sobre el género Swietenia Jacq. (Swietenioideae, Meliaceae) en Cuba - Albert Puentes, Delhy; Rodríguez Farrat, Lázaro; Vigil Escalera, Victor (Botanica Complutensis, 2002)
ALBERT PUENTES, D., RODRÍGUEZ FARRAT, L. & VIGIL ESCALERA, V. 2002. Consideraciones sobre el género Swietenia Jacq. (Swietenioideae, Meliaceae) en Cuba. Bot. Complutensis 26: 63-78.